Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10787-011-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory properties of Doxycycline and Minocycline in experimental models: an in vivo and in vitro comparative study

Abstract: Our data indicate that anti-inflammatory and antioxidant effects, involve the inhibition of iNOS and TNF-alpha, among other properties, and these encourage clinical studies of these compounds for new therapeutic applications, especially those were inflammation plays a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 49 publications
4
53
0
1
Order By: Relevance
“…Minocycline depresses the release of oxygen radicals from various types of cells, including leukocytes, and the production of nitric oxide, through its effect on nitric oxide synthase (Amin et al, 1996). Data from in vitro rat brain assays show that minocycline is an effective antioxidant, with radical scavenging potency, similarly to vitamin E (Kraus et al, 2005), confirming previous results from our laboratory (Leite et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Minocycline depresses the release of oxygen radicals from various types of cells, including leukocytes, and the production of nitric oxide, through its effect on nitric oxide synthase (Amin et al, 1996). Data from in vitro rat brain assays show that minocycline is an effective antioxidant, with radical scavenging potency, similarly to vitamin E (Kraus et al, 2005), confirming previous results from our laboratory (Leite et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Minocycline is known to present a variety of antiapoptotic and anti-inflammatory effects, and these actions are manifested at low doses of the drug, as previously observed by several models of inflammation in vivo (Leite et al, 2011).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Most conventional anti-inflammatory drugs including diclomol gel suppress inflammatory responses at the later phase of inflammation [23]. In this study, hexane fraction of C. afer balm formula suppressed xylene-induced ear thickness from 10 to 360 minutes which suggested that the anti-inflammatory activity of hexane fraction of C. afer balm formula could be through modulation of arachidonic acid metabolism.…”
Section: Discussionsupporting
confidence: 50%
“…Previously, we demonstrated a potent anti-inflammatory effect of Mino acutely administered in several models of inflammation [70]. In addition, Mino sub-chronically injected significantly reversed neurochemical and behavior alterations, in models of global ischemia and PD in rats [71].…”
Section: Discussionmentioning
confidence: 99%